Evaluation of the Performance Business Of Hand Line Yellowfin Tuna At Bacan Beach Fishery Port South Halmahera Regency - Irham, Irham; Karman, Amirul; Hi. Iksan, Kusdi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The use of yellowfin tuna in the waters of Bacan Island uses hand line fishing gear with FAD catching tools. The fishing port that is used as a landing place for the catch and the fishing base of the fishing fleets is the Bacan Coastal Fishing Port (PPP). Increasing the catch of fishermen depends on the use of production inputs. This is because the influence of production inputs is needed so that the fishing business runs optimally with the use of effective and efficient production inputs so as to increase the catch and income of fishermen. Therefore, the research was designed with the aim of evaluating the performance of the yellowfin tuna hand line fishery business which includes technical, biological, and economic aspects. The research has been carried out at PPP Bacan, for 3 months in 2021. The research uses the descriptive surev method. The results showed that the fishing gear used to catch yellowfin tuna in the waters of Bacan Island was hand line and the location of the catch was in the FAD area. The trend of catch production, fleet productivity, and FAD productivity for 5 years (2016-2020) is increasing. This fishing business is profitable and deserves to be continued. The profit value of the yellowfin tuna hand line fishing business in one year is IDR. 34,328,600.00, Net B/C ratio 1.13, IRR 33%, BEP IDR. 393,263,399.97, and PP 3.28 years. 99.96, and PP 2.86 years.